1999
DOI: 10.1161/01.hyp.34.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Preactivated Peripheral Blood Monocytes in Patients With Essential Hypertension

Abstract: Abstract-The purpose of this study was to investigate the possible involvement of human peripheral blood monocytes in the pathology of hypertensive disease. We determined the in vitro secretion patterns of proinflammatory cytokines obtained from isolated peripheral monocytes from normal controls and from hypertensive patients either after in vitro stimulation with angiotensin II (Ang II) with or without preincubation with an Ang II type 1 receptor antagonist (losartan) or after stimulation with lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(175 citation statements)
references
References 30 publications
12
162
1
Order By: Relevance
“…Our results are somehow different from those previously reported (Table 3). 6,16,21,[33][34][35][36][37] As stated by Hall et al 37 differences in assay methods, population origin and their health status, reagents, sample size, and monocyte numbers might all contribute to the differences observed among studies (Table 3). Our functional study was carried out in healthy homozygous individuals, who had not suffered from infection disease and were free of medication.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are somehow different from those previously reported (Table 3). 6,16,21,[33][34][35][36][37] As stated by Hall et al 37 differences in assay methods, population origin and their health status, reagents, sample size, and monocyte numbers might all contribute to the differences observed among studies (Table 3). Our functional study was carried out in healthy homozygous individuals, who had not suffered from infection disease and were free of medication.…”
Section: Discussionmentioning
confidence: 97%
“…A clinical study reported that the levels of IL-6 and TNF-α in plasma were correlated with blood pressure in human patients [227]. It also has been shown that hypertension spontaneously activates circulating monocytes and increases reactive oxygen species production in immune cells [228][229][230]. Using leukocyte-specific CCR2-deficient mice, Ishibashi et al [231] revealed the importance of monocyte CCR2 in hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…Transient transfections in the mouse adrenocortical tumor cell line Y-1 have shown that human renin promoter is responsive to TNF-␣ (5). On the other hand, inflammatory cytokines and particularly TNF-␣, which is an archetypal representative of the cytokine family, seem also to be engaged in blood pressure homeostasis (7,15). Thus TNF-␣ was found to be involved in the control of vascular contraction and proliferation (4,26).…”
mentioning
confidence: 99%